2009
DOI: 10.1063/1.3211863
|View full text |Cite
|
Sign up to set email alerts
|

Surface sp half-metallicity of zinc-blende calcium monocarbide

Abstract: Articles you may be interested inBulk and surface half-metallicity: Metastable zinc-blende TiSb J. Appl. Phys. 112, 023712 (2012); 10.1063/1.4739744 First-principles study on the half-metallicity of full-Heusler alloy Co2VGa (111) surface J. Appl. Phys. 111, 093730 (2012); 10.1063/1.4716183 First-principles prediction of half-metallic ferromagnetism in Cu-doped ZnS J. Appl. Phys. 107, 043913 (2010); 10.1063/1.3309771 Half-metallicity at ferromagnetic∕antiferromagnetic interfaces in zincblende transition-metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…So, the investigation of the surface effect on half-metallicity is very important. 32,[60][61][62][63][64][65][66] Here, we investigate the half-metallicity and spin-polarization depending on the terminated (001) surface for NbFeCrAl and NbFeVGe compounds. Owing to the atomic equivalent occupation in the lattice, there are two kinds of terminated (001) surface in type I structure.…”
Section: Resultsmentioning
confidence: 99%
“…So, the investigation of the surface effect on half-metallicity is very important. 32,[60][61][62][63][64][65][66] Here, we investigate the half-metallicity and spin-polarization depending on the terminated (001) surface for NbFeCrAl and NbFeVGe compounds. Owing to the atomic equivalent occupation in the lattice, there are two kinds of terminated (001) surface in type I structure.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, NaX (X ¼O, S, Se, Te and Po) [27] has been found to be half metallicity. In addition, Heusler structural GeKCa and SnKCa [28], Mg-or Ca-doped AlN [29] and SnO 2 [30], alkali dioxide RbO 2 [31], and some alkalineearth carbides and nitrides are also confirmed the existence of half metallicity [32][33][34]. Among these HMF, especially, MgN has attracted considerable attention due to its high Curie temperature and fabricated probably [35].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, Zhang [26] has reported that ZB LiC, NaC, and KC compounds are HM ferromagnets, but these compounds with RS structure show nearly HM ferromagnetic properties. Then I-V compounds (Li, Na, K) (N, P, As) have been studied in which nitrides have been found to be HM ferromagnets [27]. Recently, Gao et al [28] have done a theoretical investigation on the alkali-metals compounds MS (M = Li, Na, and K) and they have predicted that all ZB and RS MS except RS LiS are HM ferromagnets with an integer magnetic moment of 1.00μ B per formula unit.…”
Section: Introductionmentioning
confidence: 99%